Drop-on-demand E-jet printing of continuous interconnects with AC-pulse modulation on highly insulating substrates. (October 2015) - Wei, Chuang; Qin, Hantang; Chiu, Chia-Pin; Lee, Yuan-Shin; Dong, Jingyan
Abstract: In this paper, we present a novel AC-pulse modulated electrohydrodynamic (EHD) jet printing technology that enables high resolution fabrication of electrical features and interconnects using the silver nanoink on highly insulating substrates. In traditional EHD jet printing, the remained charge of the printed droplets changes the electrostatic field distribution and interrupts the follow-on printing behavior, especially for highly insulating substrates having a slow charge decay rate. In this paper, a modulated AC-pulsed voltage was used for the EHD jet printing process that can alternate the charge polarity of the consequent droplets to neutralize the residue charge on the substrate. The effect of the residue charge is minimized, which enables high resolution printing of continuous patterns. With three printing parameters (e.g. pulse frequency, voltage, and duration), the EHD jet printing speed and droplet size can be controlled independently. We demonstrated that AC-pulse modulated EHD jet printing can overcome the charge accumulation challenge on highly insulating substrates, and investigated the variables of fabrication process to achieve reliable jet printing of conductive silver tracks.